Generation of Recombinant Porcine Parvovirus Virus-Like Particles in Saccharomyces cerevisiae and Development of Virus-Specific Monoclonal Antibodies - Paulius Lukas Tamošiūnas; Rasa Petraitytė-Burneikienė; Rita Lasickienė; Artiomas Akatov; Gabrielis Kundrotas; Vilimas Sereika; Raimundas Lelešius; Aurelija Žvirblienė; Kęstutis Sasnauskas (Journal of Immunology Research)
Porcine parvovirus (PPV) is a widespread infectious virus that causes serious reproductive diseases of swine and death of piglets. The gene coding for the major capsid protein VP2 of PPV was amplified using viral nucleic acid extract from swine serum and inserted into yeast Saccharomyces cerevisiae expression plasmid. Recombinant PPV VP2 protein was efficiently expressed in yeast and purified using density gradient centrifugation. Electron microscopy analysis of purified PPV VP2 protein revealed the self-assembly of virus-like particles (VLPs). Nine monoclonal antibodies (MAbs) against the recombinant PPV VP2 protein were generated. The specificity of the newly generated MAbs was proven by immunofluorescence analysis of PPV-infected cells. Indirect IgG ELISA based on the recombinant VLPs for detection of PPV-specific antibodies in swine sera was developed and evaluated. The sensitivity and specificity of the new assay were found to be 93.4% and 97.4%, respectively. In conclusion, yeast S. cerevisiae represents a promising expression system for generating recombinant PPV VP2 protein VLPs of diagnostic relevance.